The Perception of Election Organizer and Political Actors Towards the Open Proportional System in Bantul Regency - Moch Edward Trias Pahlevi; Ridho Al-Hamdi; Achmad Nurmandi (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2020)
The electoral system influences various other systems such as party systems and government systems. It also affects the psychology of voters (constituents). An open proportional system encourages a high electoral violations and also encourage candidates to compete in mobilizing mass support for their victory. The efforts to seek mass votes are carried out in a pragmatic way, mobilizing the masses by forming a network team and equipping them with some money or other items. An open proportional system impacts election violations in Bantul Regency. It can be seen from the data Bawaslu of Yogyakarta Province. Bantul Regency received the title with the highest election violations in the Special Region of Yogyakarta. Many things cause this to happen, one of the biggest causes is the open proportional system and also Bantul Regency received the title of highest voter turnout in the Special Region of Yogyakarta. Of course this is inseparable from the application of an open proportional system. However, this high participation rate is being debated by many parties because the high number is due to the role of political actors who act pragmatically to mobilize voters to come to the polling stations. This research uses a qualitative approach and analysis carried out using Nvivo 12 plus software. The purpose of this research are to determine the perception of election organizers and political actors to open proportional system. The results of this research are the perception of election organizers and the major political actors assume an open proportional system have a negative impact. This negative impact caused by the proportional system which resulted in a fairly high political pragmatism that has implications for the high electoral violations in Bantul and open proportional system also makes the quality of the public considered to be bad in the election event. Furthermore, the attitude of the election organizers and the majority of political actors answered that they did not agree with the open proportional system that was still used in Indonesian elections.